Acupuncture as an Add-On Treatment for Functional Dyspepsia: A Systematic Review and Meta-Analysis - Kwon, Chan-Young; Ko, Seok-Jae; Lee, Boram; Cha, Jae Myung; Yoon, Jin Young; Park, Jae-Woo (Frontiers in Medicine, 2021)
Background: We aimed to critically evaluate the effectiveness and safety of acupuncture as an add-on therapy to conventional Western medication (WM) and assess the quality of evidence (QoE) of these findings. Methods: A total of 12 English, Korean, and Chinese databases were searched on December 18, 2020. Randomized controlled trials (RCTs) assessing the effectiveness of acupuncture as an add-on therapy to conventional WM for functional dyspepsia (FD) were included. The primary outcome was the symptom score of FD. The risk of bias of the included studies and QoE were evaluated using the Cochrane Collaboration’s risk of bias tool and Grading of Recommendations, Assessment, Development, and Evaluation method, respectively. Results: A total of 22 RCTs were included. The total and individual FD symptom scores were significantly improved in the acupuncture combined with WM groups compared with the WM alone groups, except for in one study. The Nepean dyspepsia index score and total effective rate mostly improved significantly in the acupuncture group, regardless of the WM used and acupuncture type. FD-related biomarkers, such as ghrelin and gastrin levels, showed mixed results. The acupuncture group showed a significantly lower recurrence rate after three to six months of follow-up than the WM alone group. There were no differences in the incidence of adverse events between the two groups. The included studies generally had low methodological quality. The QoE for the main findings was generally very low to moderate. Conclusion: Limited evidence suggests that acupuncture has the potential to improve FD treatment in combination with conventional WM. Furthermore, the methodological quality of the included studies and QoE of the main findings were generally low. Therefore, RCTs with a rigorous methodology, including sham acupuncture and multiethnic subjects, should be performed. Protocol registration number: PROSPERO (registration number: CRD42021226608) and OSF registries (URL: https://osf.io/mxren)